2002
DOI: 10.1111/1467-7660.00248
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up Participatory Watershed Development in India

Abstract: Participation' is widely accepted as a prerequisite to successful watershed development in India, but there is no shared understanding of its meaning, nor of how to make it operational. Meaningful participation, in which communities work collectively, help make decisions and share costs, is limited primarily to projects implemented by non-governmental organizations (NGOs). Participation in government projects is more superficial because staff lack the skills and incentive to engage in meaningful participation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…However, if farmers are engaged in a facilitated, interactive learning environment which enables them to play around with the technology within their specific environments (i.e., to innovate), compare results with their peers, and see impacts as they emerge, then their initial judgement of the technology can change (Pannell et al 2006;Bentley et al 2007). Some additional factors influencing the scaling out process were cited as socio-economic and cultural diversity across communities or areas, the quality of community participation, communication between development partners, and enabling government policies and resources (Gundel et al 2001;Kolavalli and Kerr 2002;World Bank 2003;Gillespie 2004).…”
Section: Dimensions Of Scaling Out and Up Based On Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if farmers are engaged in a facilitated, interactive learning environment which enables them to play around with the technology within their specific environments (i.e., to innovate), compare results with their peers, and see impacts as they emerge, then their initial judgement of the technology can change (Pannell et al 2006;Bentley et al 2007). Some additional factors influencing the scaling out process were cited as socio-economic and cultural diversity across communities or areas, the quality of community participation, communication between development partners, and enabling government policies and resources (Gundel et al 2001;Kolavalli and Kerr 2002;World Bank 2003;Gillespie 2004).…”
Section: Dimensions Of Scaling Out and Up Based On Experiencesmentioning
confidence: 99%
“…Partnerships between government and non-governmental organizations (NGOs) can further extend beneficial technologies from research to the poor, while also building capacity of scientists to understand social and poverty related issues (Kolavalli and Kerr 2002). Such networks not only spread the costs of scaling out, they also spread the word and bring diverse roles to enabling scaling out of technologies or participatory approaches.…”
Section: Institutional Support and Partnershipsmentioning
confidence: 99%
“…A range of case studies reported factors that favour successful scale out of technologies including, clear and tangible benefits for farmers, strong leadership, peer learning, support from officials and donors, availability of credit and security of land tenure, a strong civil society, socio-economic and cultural diversity across communities or areas, the quality of community participation, communication between development partners, and enabling government policies and resources (Gundel et al, 2001;Kolavalli and Kerr, 2002;World Bank, 2003;Gillespie, 2004;IIRR, 2000). If research scientists and extension workers are working towards scaling out useful technologies, they need to have a sound understanding of how farmers learn, how they experiment and innovate, and how local decisions are made in the family and social structures (Scoones and Thompson, 1994;Cary et al, 2002;Pannell et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This has been developed further in the work the International Society of Ecosystem Health (see the various issues of Ecosystem Health, and Costanza et al, 1992;Rapport et al, 2002;Kay and Scheneider, 1994;and Kay et al, 1999). Not linked to this stream, but developing in parallel, has been the increasing use in developing countries, especially India, of ecosystem approaches to natural resource management through the concept of integrated watershed management, as a strategy to rebuild agriculture and promote participatory development (Vaidyanathan, 1991;Kolavalli and Kerr, 2002).…”
Section: Introductionmentioning
confidence: 99%